Composite Carbon Nanotube and Titania Catalyst Supports for Enhanced Activity and Durability - Rigdon, William A.; Larrabee, Diana; Huang, Xinyu (ECS transactions, 2013)
In polymer electrolyte cells, an approach is shown for construction of resilient electrocatalysts. In the anode where the hydrogen oxidation reaction is subject to poisoning from fuel impurities like carbon monoxide (CO), increased tolerance and stability for the catalyst is revealed by modification of the support structure and properties. A carbon nanotube framework serves as the foundation for metal oxide addition, namely titania and niobium doped form. The corrosion resistant transition metal oxides form a strong bond with platinum catalysts through unique electronic interactions, measured by XPS. Several other material characterizations are also included to make comparisons between composites. Composite supports contribute improved reactivity towards oxidation of CO, especially in reduced titania. Carbon corrosion resistance is also measured and shown to be the greatest for this support. Synergistic combination of effects is observed directly by preparation of electrocatalysts into working membrane electrode assemblies measured for their performance & durability.